FRAÇÕES FÍSICAS DA MATÉRIA ORGÂNICA DO SOLO E ÍNDICES DE MANEJO DE CARBONO EM DIFERENTES SISTEMAS DE MANEJO - Faria, Elias; Rosset, Jean; Bispo, Luan; Dos Santos, Thais; Marciano, Marra; Castilho, Selene (ANAIS DO ENIC, 2018)
-